2020
DOI: 10.3389/fneur.2020.00193
|View full text |Cite
|
Sign up to set email alerts
|

Probing Context-Dependent Modulations of Ipsilateral Premotor-Motor Connectivity in Relapsing-Remitting Multiple Sclerosis

Abstract: Objective: We employed dual-site TMS to test whether ipsilateral functional premotor-motor connectivity is altered in relapsing-remitting Multiple Sclerosis (RR-MS) and is related to central fatigue.Methods: Twelve patients with RR-MS and 12 healthy controls performed a visually cued Pinch-NoPinch task with their right hand. During the reaction time (RT) period of Pinch and No-Pinch trials, single-site TMS was applied to the left primary motor cortex (M1) or dual-site TMS was applied to the ipsilateral dorsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Moreover, longer cSP duration ( Nantes et al, 2016 ) or triple stimulation technique ( Hofstadt-van Oy et al, 2015 ) did not correlate with cognitive performance in relapsing-remitting MS. However, central mechanisms of fatigue, that can, at least in part, play a role in cognitive performances, appeared related to changes in cortical excitability, especially increased interhemispheric inhibition ( Chalah et al, 2018 ) or SICI ( Chalah et al, 2019 ), as well as attenuation of premotor-motor functional connectivity ( Ruiu et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, longer cSP duration ( Nantes et al, 2016 ) or triple stimulation technique ( Hofstadt-van Oy et al, 2015 ) did not correlate with cognitive performance in relapsing-remitting MS. However, central mechanisms of fatigue, that can, at least in part, play a role in cognitive performances, appeared related to changes in cortical excitability, especially increased interhemispheric inhibition ( Chalah et al, 2018 ) or SICI ( Chalah et al, 2019 ), as well as attenuation of premotor-motor functional connectivity ( Ruiu et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the non-fatigue state, the lack of pre-movement facilitation correlated with the amount of self-reported fatigue ( Morgante et al, 2011 ). Furthermore, in a former study including a subgroup of subjects participating in the current study, we applied dual site TMS over the ipsilateral dorsal premotor cortex (PMd) and the M1 and found that the self-experienced fatigue scaled positively with an attenuation of premotor-to-motor functional connectivity ( Ruiu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 90%
“…A transcortical magnetic stimulation study in RRMS–patients found an attenuated connectivity between premotor- and primary motorcortex which was significantly correlated with reported motor fatigue. In contrast, corticospinal connectivity was retained ( 31 ).…”
Section: Introduction: Fatigue In Multiple Sclerosismentioning
confidence: 99%